The Effects of Phytase and Different Level of Dietary Calcium and Phosphorous on Phytate Phosphorus Utilization in Laying Hens - Musapuor, A.; Pourreza, J.; Samie, A.; Shahrbabak, H. Moradi (International Journal of Poultry Science, 2005)
This experiment was conducted to study the effects of different levels of phytase (0, 500 and 1000 FTU/kg diet), calcium (2.275 and 3.25 percent) and available phosphorus (0.175 and 0.25 percent) on phytate phosphorus utilization in laying hens. One hundreds ninety two 30-week age White Leghorn (Hy-line W-36) laying hens were randomly allocated in cages for 12 dietary treatments with arranged of 3*2*2 factorial experiment with four replicates and four hens per replicate. The experimental period lasted 90 days, when the age of hen was 42 weeks. Dietary phytase caused a significant (P< 0.05) increase in feed consumption, feed conversion ratio, tibia ash weight, tibia ash percentage, tibia phosphorus, plasma phosphorus and phosphorus digestibility. However, dietary phytase caused a significantly (P< 0.05) decrease in plasma alkaline phosphatase activity and excreta phosphorus percentage. Also phytase had no beneficial effect on egg shell quality traits. Available phosphorus levels had significant effect (P< 0.05) on tibia ash weight and tibia ash percentage. Reduction dietary available phosphorus caused a significant (P< 0.05) decrease in feed consumption. Effect of dietary calcium were significant (P< 0.05) on tibia ash weight, feed consumption and plasma phosphorus. Interaction between phytase and calcium on tibia phosphorus, plasma calcium and excreta phosphorus were significant (P< 0.05). Interaction between phytase and available phosphorus on tibia phosphorus were significant (P< 0.05). Overall, it could be concluded that in low phosphorus diet which food consumption is low, phytase would increase food consumption as well as retention of phosphorus in bones. Also, the lower excreta of phosphorus by using phytase could decrease pollution.